The long war on drugs - Foster, Anne L. (Duke University Press, 2023)
"Since the early twentieth century, the United States has led a global prohibition effort against certain drugs in which production restriction and criminalization are emphasized over prevention and treatment as means to reduce problematic drug usage. This "war on drugs" is widely seen to have failed, and periodically de-criminalization and legalization movements arise. Debates continue over whether the problems of addiction and crime associated with illicit drug use stem from their illicit status or the nature of the drugs themselves. In The Long War on Drugs Anne L. Foster explores the origin of the punitive approach to drugs and its continued appeal, despite its obvious flaws. She provides a comprehensive overview, focusing not only on a political history of policy developments, but also on changes in medical practice and knowledge of drugs. Foster also outlines the social and cultural changes prompting different attitudes about drugs, the racial, environmental, and social justice implications of particular drug policies, and the international consequences of US drug policy"--